Factors associated with early clinical remission in patients with idiopathic retroperitoneal fibrosis - Chao, Yuyan; Li, Rong; Shao, Yuxia; Fei, Yunyun; Zhou, Jiaxin; Zhao, Lidan (Rheumatology (Oxford, England), 2025)
Idiopathic retroperitoneal fibrosis (IRF) is a rare autoimmune-mediated condition characterized by fibro-inflammatory tissue development around the abdominal aorta and iliac arteries. Ureteral entrapment and hydronephrosis are the most common manifestations and acute renal failure or chronic renal insufficiency may occur as the consequence. Glucocorticoids and immunosuppressants may be effective but the therapeutic response and outcome are heterogeneous and hard to predict. This study aimed to investigate the factors associated with early remission in patients with IRF. This retrospective study included 91 IRF patients who visited Peking Union Medical College Hospital between May 2013 and December 2023. Clinical data and outcomes were reviewed, and the time to remission was calculated. Over a median follow-up of 2.63 years (IQR, 1.29-3.41), 38 patients achieved remission within six months after treatment initiation. In multivariable analysis, male gender (OR 5.297, 95% CI 1.445-19.420, P=0.012) and higher baseline complement component 3 (C3) (OR 2.153, 95% CI 1.131-4.097, P=0.019) levels were significantly associated with early clinical remission (≤6 months). The time to remission was negatively associated with C3 levels (r =-0.243, P=0.014). Patients with high C3 levels (≥1.144 g/l) tended to achieve remission in a shorter time than their counterparts with low C3 levels(<1.144 g/l) (P=0.028). An effective nomogram model for predicting disease remission was constructed with gender and C3 (AUC=0.73, 95% CI 0.62-0.84). Male gender and higher baseline C3 levels may act as potential predictors for achieving early remission in patients with IRF.